Effects of Tree Age and Bole Section on Pulpwood of Korean Spruce (Picea koraiensis Nakai) - Junhui Wang; Hongjie Zhang; Ming Lei; Huiren Hu; Pertti Pulkkinen (BioResources, 2014)
Korean spruce (Picea koraiensis Nakai) is one of the most important wood resources for pulp and paper industry. However, a long production cycle is required for spruce to obtain mature timber, which may negatively influence the biomass production. In this study, fiber morphology, chemical composition, and pulping properties of Korean spruce with different tree ages and vertical locations were investigated. The results show that, along with the increase of tree ages, the contents of extractives, lignin, and pentosan increase to different extents. There are also some differences of pulping properties with different tree ages. As a pulpwood, the Korean spruce with tree ages of around 22 to 32 years is more suitable for kraft pulping, compared to that with 32-46 years. In addition, the middle segment of the bole had better pulp strength properties than the upper or lower bole segments.